Formulation and Analysis of Solid Bath Soap with The Addition Of Seaweed: Formulasi dan Analisis Mutu Sabun Mandi Padat dengan Penambahan Rumput Laut - Nurhajawarsi (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
Nowdays bath soap that is widely used by the public is soap made from sodium laurate sulphate (SLS) surfactants. For some people who have sensitive skin, it can cause mild to severe irritation. So that consumers are now starting to increase interest in natural soap (saponification soap). Research has been carried out by varying the formula of solid bath soap with the addition of seaweed as a rich source of active substances such as vitamin E and its activity as an antiseptic. This study aims to obtain the acceptable formulation of solid bath soap from seaweed and to analyze the quality of the seaweed soap according to SNI 3532: 2016 parameters. There are 3 variants of the formula made by the hot process method. The best formula that fulfills the SNI 3532: 2016 solid bath soap quality standards were formula F2 with a pH of 9; 0.791% water content; 0.048% free alkaline; 2.6 cm foam stability. In organoleptic testing, each formula obtained a good level of acceptance and did not show any significant differences.